(3QSGdI GdJdHjI hGdJCfjH hGdJhHjN hGdJhbjas - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3ChUdJ Edi eYO Hf eMeO hEdi ef eYg HGdbGgQI ef GdebUQjf ai GdSfI GdQGHYI YTQ ef Sfjf bGFe GdReGf bhHdJ hUMJ GdMeO dhdi GdfYeI hehdgG s
(3BNQgG (B:s
(3hGdLhGH HeG aYdJ hGddg jhab ef SYi ai eQVGJg hjLRd KhGH GdTGcQjf hGdMeO dehdGfG hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B42s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis